Penerapan Teori Pidana dalam Pencegahan dan Penanggulangan Kriminalitas: Studi Kasus dan Tantangan Implementasi - Hafid, Numan Sofari; Rusmana, Dian; Shaleh, Chaerul (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
Ideally, the application of criminal law theory in the prevention and handling of criminality in Indonesia should be able to respond to the dynamic social changes and evolving nature of crime. Criminal law policy should not only focus on enforcement aspects but also on comprehensive prevention, integrating social approaches and legal education as part of preventive strategies. This is essential for the Indonesian criminal justice system to be more effective in reducing crime rates and improving the legal system as a whole. The aim of this research is to analyze the application of criminal law theory in the prevention and handling of criminality, as well as to identify the challenges in implementing these theories through case studies. This article falls under qualitative research, using a descriptive-analytical approach aimed at describing and analyzing the application of criminal law theory within the context of Indonesian law. The research results show that the application of criminal law theory in crime prevention and control faces challenges in regulation, law enforcement, and social response, often creating a gap between the ideal concept and practical implementation. Therefore, an integrative approach that considers normative, sociological, and empirical aspects is needed to ensure the effectiveness of criminal law policies in achieving justice and public protection.